Outcome following late reperfusion with PCI in stable patients with ST-segment elevation myocardial infarction presenting more than 12 hours from onset of symptoms. (2nd May 2022) - Moura, A; Castilho, B; Saraiva, M; Craveiro, N; Domingues, K; Martins, VP
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: 8-40% of patients with acute ST-elevation myocardial infarction (STEMI) present later than 12 hours after symptom onset. According to guidelines these late presenters maintain indication for primary percutaneous coronary intervention (PCI) when there are signs of ongoing ischemia. However, it prevails uncertainty in relation to the best approach in stable late presenters. Aims: Describe the profile of stable late STEMI presenters and evaluate the trends of reperfusion decision in the Portuguese reality; compare early term outcomes between patients submitted to emergent primary PCI and those in which it was preferred an initial conservative approach. Methods: Retrospective analysis of patients with STEMI presenting ≥12-48h hours after the beginning of the symptoms between October 2010 and December 2019 without evidence of ongoing ischemia, inserted in a national registry of acute coronary syndromes. Patients were dichotomized and compared according to whether or not were submitted to emergent reperfusion based on primary PCI. Results: 274 patients were included (2.3% of all STEMI), predominantly men (67.5%), with a mean age of 68±13 years old. Emergent PCI was performed in a minority (15.7%; n=43); even so, coronarography ended up being executed in 61.3% of the admissions, with angioplasty performed in 47.1% of the cases. Right coronary artery was the most common intervened vessel (50.8%). Inotropes were necessary in 4.6% of the patients, with no reports of ventricular assistance device use. Mean ejection fraction was 51±12% with no differences between groups. Patients submitted to emergent PCI (15.7%) had a lower prevalence of atrial fibrillation (0 vs. 9.3%, p=0.04) and had more commonly electrocardiographic criteria for anterior STEMI (64.3% vs. 41.4%, p=0.006). Nitrates were significantly less prescribed at discharge in this subgroup (4.9% vs. 26.8%; p=0.002). Apart from aborted cardiac arrest, that was more prevalent in patients submitted to emergent reperfusion (4.8% vs. 0.9%, p=0.12), it was observed a tendency toward a lower percentage in this subgroup in all other early hard clinical outcomes such as re-infarction (0 vs. 0.4%, p=1.00), mechanical complications (0 vs. 2.2%; p=1.00), sustained ventricular tachycardia (0 vs. 0.9%, p=1.00) and in-hospital death (0% vs. 4.4%, p=0.37). However, none of the differences have reached statistical significance. Conclusion: The study shows that, in the Portuguese reality, emergent reperfusion is adopted in only a minority of late stable STEMI patients, with a clear tendency to perform it more frequently in subacute anterior STEMI. Emergent PCI strategy did not show a clear benefit in terms of left ventricular function, risk of re-infarction, arrhythmic and mechanical complications, and in-hospital death. On the other hand, there was apparently a significant advantage of this strategy in ischemic symptom control.